In vitro α-amylase and α-glucosidase inhibition and increased glucose uptake of morinda citrifolia fruit and scopoletin - Khamsah Suryati, Mohd; Ahmad Zubaidi, A.Latif; U.S. Mahadeva, Rao (2015)
Diabetes mellitus is a metabolic disorder and management of blood glucose level is an important strategy in the control of the disease and complications associated with it. Therefore, components that cause uptake of glucose from the bloodstream and inhibitors of carbohydrate hydrolyzing enzymes can be useful in treatment of diabetes and medicinal plants are often used to achieve this aim. Morinda citrifolia fruit (MCF) is used in various countries for treatment of diabetes and the purpose of this study was to investigate the effect of MCF extract and its biomarker scopoletin on glucose uptake in HepG2 cells as well as its inhibitory effect on α-amylase and α-glucosidase. The safe doses for MCF extract and scopoletin were at 1 mg/ml and 0.2 μM, respectively as assessed by MTT assays and these were used for the assays. The extract had glucose uptake of 59.5% which was comparable to the standard metformin whereas the value for scopoletin was 30.6%. The extract had mild inhibitory activity on α-amylase and α-glucosidase with percentage of inhibition at 43.5% and 57%. The biomarker scopoletin showed lower activities at 23.9% and 35.7% for α-amylase and α-glucosidase respectively. Hence, these three activities may possibly be the mechanisms for MCF to exert its antidiabetic activity.